Great philosophers and thinkers on education - Aggarwal, J. C.; Gupta, S. (India : Shipra Publications, 2006)
The field of education has grown enormously. Philosophers and thinkers on education throughout the world continue to enrich the professional literature with their important contributions.
Preface -- 1. A.N. Whitehead (1861-1974) -- 2. Abraham Lincoln (1809-1865) -- 3. Abul Kalam Azad (1888-1958) --- 4. Annie Besant (1847-1933) -- 5. Aristotle (384-322 B.C) -- 6. Aurobindo Ghose (1872-1950) -- 7. A.P.J Abdul Kalam (1931- ) -- 8. B.R Ambedkar -- 9. Bal Gangadhar Tilak (1856-1920) -- 10. Bertand Russell (11872-1970) -- 11. Confucius (551-479 B.C) -- 12. Emile Durkheim (1858-1917) -- 13. Eramus Desiderius (1467-1536) -- 14. Frederich August Froebel (178201852) -- 15. Gijubhai Badheka (1885-1917) -- 16. Gopal Krishan Gokhale (1866-1915) -- 17. Herbert Spencer (1820-1903) -- 18. Immanuel Kant (1724-1804) -- 19. Isaac Susan (1895-10948) -- 20. Jan Amos Comenius (1502-1670) -- 21. Jawaharla Nehru (1889-1964) -- 22. Jean Jacques Rousseau (1712-1778) -- 23. Jiddu Krishnamurti (1895-1986) -- 24. John Dewey (1857-1986) -- 25. John Henrich Pestalozzi (1746- 1827) -- 26. K.G. Saiyidain (1904-1071) -- 27. Leo Tolstoy (1828-1910) -- 28. M.K Gandhi (1869-1948) -- 29. Maria Montessori (1870-1952) -- 30. Marshall McLuhan (1972-1980) -- 31. Michael De Montaigne (1533-92) -- 32. Paramhansa Yogananda (1893-1952) -- 33. Paulo Freire (1922-1977) -- 34. Plato (427-347 B.C.) -- 35. Rabindranath Tagore (1861-1941) -- 36. Sarvepalli Radhakrishnan, Dr. (1888-1975) -- 37. Shankara Acharya (788-820 A.D.) -- 38. Socrates (469-399 B.C.) -- 39. Swami Dayananda (1825-1883) -- 40. Swami Vivekanda (1863-1902)) -- 41. T.P Nunn (1870-1944) -- 42. Tarabhai Modak (1892-1973) -- 43. Zakir Hussain (1897-1969) -- 44. Brief Notes: Western and Indian Educational Philosopers and Thinkers
Includes index.
Keywords: PHILOSOPHY